EFFECT OF VALUE PROPOSITION AS A MARKETING STRATEGY ON INNOVATIVE CAPACITY OF THE PERFORMANCE OF PHARMACEUTICAL FIRMS IN KWARA STATE - Nurudeen Bello Ahmed; Aminu Nasir Brimah; Aremu Abdulganiyu Bello (Malete Journal of Accounting and Finance)
There is a lot of believe that marketing starts and ends in product or service delivery. This believe and many more envelop most companies focusing on selling of the product with little or no emphasis on the level of product satisfaction on customers. On the basis of this, this study examines the impact of Value Proposition as a Marketing Strategy for Innovative Capacity of pharmaceutical firms in Kwara State of Nigeria. The study adopted a cross sectional survey design, involving the use of structured questionnaire as research instruments. The population comprises of the 283 employees in the manufacturing pharmaceutical firms in Kwara State and employed the convenience sampling techniques to arrive at a sample of 169 respondents. The study adopted the use of structural equation model to analyse the data. The result of the study as (0.365,0.594 and 0.224) reveals that value proposition as a marketing strategy has significant effect on innovative capacity of pharmaceutical firms in Kwara State. Furthermore, the relationship between Value Proposition and Innovative Capacity as a marketing strategy impacts on the performance of pharmaceutical firms in Kwara State of Nigeria. Therefore, the study recommends that to enhance the innovative capacity of the firms, managers should be conscious of the product usability and the product style.